2002
DOI: 10.1097/00000374-200208000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Induces Morphological and Dynamic Changes on In Vivo and In Vitro Neural Crest Cells

Abstract: Taking into account that even a limited period of abnormal behavior may imply serious consequences in the final cues of an embryonic cell population, our results indicate that the biological effects of ethanol on early development-even during a short time-could induce permanent ontogenetic perturbations of NCCs, with potentially dramatic effects on embryonic morphogenesis. These results support an important participation of NCCs in the etiopathogeny of FAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 41 publications
1
32
1
Order By: Relevance
“…However, our results are not consistent with this view because at the critical period of ethanol teratogenicity, namely prim-6 and prim-16 , the neural crest cells of the zebrafish have already completed migration into the pharyngeal arches [58][66]. Thus it is possible that at least some of the hypoplasia of the pharyngeal arches seen in our study could be due to effects on postmigratory neural crest cells, in contrast to studies in chick and mouse embryos that suggest ethanol to have a major effect on migratory crest cells [9], [67]–[69]. Whether these differences are due to fundamental differences in the responses of these model species remains to be determined.…”
Section: Discussioncontrasting
confidence: 54%
“…However, our results are not consistent with this view because at the critical period of ethanol teratogenicity, namely prim-6 and prim-16 , the neural crest cells of the zebrafish have already completed migration into the pharyngeal arches [58][66]. Thus it is possible that at least some of the hypoplasia of the pharyngeal arches seen in our study could be due to effects on postmigratory neural crest cells, in contrast to studies in chick and mouse embryos that suggest ethanol to have a major effect on migratory crest cells [9], [67]–[69]. Whether these differences are due to fundamental differences in the responses of these model species remains to be determined.…”
Section: Discussioncontrasting
confidence: 54%
“…Cell death in the frontonasal process, which is mainly derived from CNCC, and the forebrain is one of the most accepted mechanism underlying FAS craniofacial and nervous system phenotypes [43]. Primary cultures of CNCC from mouse [13] and chick [12] show increased cell death in EtOH treated cultures. Additionally, experiments performed in ovo , where EtOH was injected directly into the chick egg, also reported increased cell death of CNCC [9], [11].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies in chick have reported cell death in neural crest cells [11]. In vitro analysis of CNCC has shown that EtOH exposure produces permanent changes in cell shape, surface morphology, migration, and cell death [12], [13]. Interestingly no analysis of migration defects have been reported in vivo , although histological studies have suggested the occurrence of EtOH-induced migration defects, based on the pattern of immunostained neural crest in treated chick embryos [14].…”
Section: Introductionmentioning
confidence: 99%
“…β-Catenin also has important roles in later neural crest development, through its interactions with cadherin to promote neural crest migration (de Melker et al 2004; De Calisto et al 2005) and though its transcriptional stimulation of melanocyte and sensory neuron specification (Dorsky et al 1998; Lee et al 2004). Ethanol’s dysregulation of β-catenin may not be limited to the premigratory neural crest period and could potentially explain the impaired neural crest migration (Rovasio and Battiato, 1995, 2002) and sensory deficits associated with prenatal alcohol exposure. It will be important to determine if the effects upon β-catenin reported here are stage and cell type dependent or instead reflect a broader impact of ethanol upon β-catenin activity.…”
Section: Discussionmentioning
confidence: 99%